2008
DOI: 10.1074/jbc.m708536200
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Factors Contributing to the Stability and Solubility of Autonomous Human VH Domains

Abstract: We report a comprehensive analysis of sequence features that allow for the production of autonomous human heavy chain variable (V H ) domains that are stable and soluble in the absence of a light chain partner. Using combinatorial phage-displayed libraries and conventional biophysical methods, we analyzed the entire former light chain interface and the third complementarity determining region (CDR3). Unlike the monomeric variable domains of camelid heavy chain antibodies (V H H domains), in which autonomous be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(168 citation statements)
references
References 69 publications
(34 reference statements)
10
154
4
Order By: Relevance
“…This resulted in increased hydrophilicity of the VH surface, which is normally interfaced with the VL. 16 A similar result was observed in another study on the VH single domain antibodies HEL4 and DP47d, which are highly and poorly soluble, respectively. 40 In contrast to DP47d, HEL4 has a glycine at position 35.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This resulted in increased hydrophilicity of the VH surface, which is normally interfaced with the VL. 16 A similar result was observed in another study on the VH single domain antibodies HEL4 and DP47d, which are highly and poorly soluble, respectively. 40 In contrast to DP47d, HEL4 has a glycine at position 35.…”
Section: Discussionsupporting
confidence: 71%
“…A structural study of a VH single domain antibody revealed that mutation of H35 to glycine or alanine increased solubility, expression, and thermostability. 16 The H35 glycine mutation created a cavity into which an adjacent tryptophan at position 95 became buried. This resulted in increased hydrophilicity of the VH surface, which is normally interfaced with the VL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate our hypotheses related to the design of domain antibody inhibitors of amyloid assembly, we first sought to optimize the biophysical properties of a V H antibody scaffold for CDR grafting (4,8,9). We find that gammabodies presenting hydrophobic Aβ peptide segments (e.g., Aβ residues 15-24 and 33-42) within their third CDR (CDR3) readily aggregate when heated, stick to size-exclusion columns, and express at relatively low levels (5-7 mg/L) (4,9).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate our hypothesis that antibodies grafted with Aβ amyloidogenic motifs would selectively recognize aggregated Aβ conformers, we first sought to identify an antibody scaffold that is highly stable and tolerant to grafting diverse peptide segments into its CDR loops. We selected an antibody domain (V H ) scaffold that is highly soluble and stable, and whose folding is insensitive to mutations in its third CDR (CDR3) loop (28). We find this antibody is well expressed in bacteria (>5 mg∕L), secreted into the bacterial media without cell lysis, highly pure after a single chromatography step (>95% purity), and stably folded (Fig.…”
Section: Antibody Domains Displaying Amyloidogenic Aβ Motifs Recognizementioning
confidence: 99%